Reflection of Qajar Period Social Discourse in Mastooreh Kurdestani Poems With the Approach of Norman Fairclough - Mahin Panahi; Faezeh waezzadeh (مطالعات اجتماعی روان‌شناختی زنان)
This research has been done with the aim of analyzing how the social discourse governing Qajar period Iran is reflected in the poems of Kurdistan mystic, poet lady and mystic of this period. For this purpose, the collection of Kurdistan poems has been evaluated using Norman Fairclough's critical discourse analysis approach, in three levels: description (linguistic features of the text), interpretation (relationship between text and interaction) and explanation (relationship between interaction and social context). Also, the statistical analysis of the findings has been done using Maxqda qualitative analysis software. According to the findings, although the Kurdistan mystic is subordinate to the traditional discourse both in the category of poetry and in the field of mysticism, however, his various criticisms include criticism of the political situation, criticism of economic and livelihood disorders, criticism of disorder in the field of religion and ethics, etc. The fact that he clearly reflected the general situation of Iranians in the Qajar period shows the type of his performance against the ruling discourses in this period, which is based on protest and criticism. Based on the results of the analysis, Kurdistan is primarily a mystic, but at the same time he is a poet, writer, researcher and social critic; she has played a role and expressed herself in different political, social and cultural fields much more and more advanced than the women poets or mystics in the history of Persian poetry.